(untitled) (Voice of History, 2025)
The history of drug use in Nepal is complicated and has been influenced by open borders, traditional cannabis cultivation, and changing government regulations. Drug use has increased even after the Narcotic Drugs (Control) Act of 1976 made drugs illegal, especially among young people. The origins and dissemination of drugs in Nepal, their effects on the economy, and the efficacy of legal frameworks are all examined in this article. To provide a descriptive and analytical account, the study adopts a doctrinal and narrative policy review approach and relies on secondary literature, government reports, and primary legal documents. The results indicate that although the cannabis trade used to bring in regulated revenue for the state, an important economic opportunity was lost when it was outlawed due to outside pressure. The findings reveal that prohibitionist policies have failed to reduce drug use and instead led to the criminalization of users, while also eliminating a potential source of revenue. The study concludes that Nepal needs a well-rounded drug policy that regulates cannabis under state control, prioritizes supervision of pharmaceutical drugs, rehabilitation and harm reduction. These steps would not only be in line with best practices around the world, but they would also be better for Nepal’s own social and economic situation.